2013
DOI: 10.3390/ijms140816515
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations in Articular Cartilage Matrix Are Associated with Early-Onset Osteoarthritis in the Spondyloepiphyseal Dysplasia Congenita (Sedc) Mouse

Abstract: Heterozgyous spondyloepiphyseal dysplasia congenita (sedc/+) mice expressing a missense mutation in col2a1 exhibit a normal skeletal morphology but early-onset osteoarthritis (OA). We have recently examined knee articular cartilage obtained from homozygous (sedc/sedc) mice, which express a Stickler-like phenotype including dwarfism. We examined sedc/sedc mice at various levels to better understand the mechanistic process resulting in OA. Mutant sedc/sedc, and control (+/+) cartilages were compared at two, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Chondrocytes within articular cartilage are surrounded by a pericellular matrix (PCM) which is composed primarily of Type VI collagen and other proteins [13,14,15]. The chondrocyte PCM has a stiffness of ~25–200 kPa [16] which is diminished in OA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chondrocytes within articular cartilage are surrounded by a pericellular matrix (PCM) which is composed primarily of Type VI collagen and other proteins [13,14,15]. The chondrocyte PCM has a stiffness of ~25–200 kPa [16] which is diminished in OA [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that the heterozygous sedc mouse, although morphometrically normal, exhibits early onset OA [9]. This puzzle was solved, in part, when we demonstrated using electron microscopy that compared with controls, mutant articular cartilage displayed decreased fibril diameter concomitant with increases in size of the pericellular space, Mankin and OARSI scores, cartilage thickness, chondrocyte clustering, proteoglycan staining and horizontal fissuring [13]. We concluded that collagen in the mutant's articular cartilage (both heterozygote and homozygote) fails to provide the normal meshwork required for matrix integrity and overall cartilage stability.…”
mentioning
confidence: 88%
“…tidemark, in murine knee joints was actually detected with a Safranin-O stain [29], we devised this study. We set out to determine if the delineating tidemark is in fact an area of active metabolic calcification and whether it progresses toward the apical surface of the cartilage as OA progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Mmp-13 is a matrix metalloproteinase that digests Type II collagen and ultimately contributes to the mechanical destabilization of the ECM [29]. Mmp-13 has also been associated with inflammation triggered OA [26,30].…”
Section: Introductionmentioning
confidence: 99%